Pembelajaran Legenda Tiongkok pada Mahasiswa Pendidikan Bahasa Mandarin di Universitas Negeri Malang melalui Podcast Teatime Chinese - Liliana Wida Larassari Ismianto; Lilis Afifah; Octi Rjeky Mardasari (Jurnal Bahasa dan Sastra, 2023)
Podcast as learning media are believed to enlarge learners' motivation when learning a foreign language. In Chinese Literature History (CLH) course, the most difficult material faced by students of the Chinese Language Education Study Program at State University of Malang (CLESP UM) is fairy tales and legends. Students said that this theme will be easier to understand if it is presentive in audio form. Therefore, this study aimed to describe the use of the TeaTime Chinese 茶歇中文 [Chá Xiē Zhōngwén] podcast in the CLH course by means of students of the CLESP UM and to describe students responses to the utilization of the podcast media. This research used descriptive qualitative method with observation and questionnaire sheets as instruments. The first instrument was filled out by two observers and the second was filled out by 46 students of CLESP UM class of 2021. The results show that the utilize of the TeaTime Chinese 茶歇中文 [Chá Xiē Zhōngwén] podcast in the CLH course run well. Moreover, the questionnaire results depict that this podcast gain positive responses from students. They are able to understand the content of the podcast easier, find intrinsic and extrinsic elements in the story, and make cultural connections between China and Indonesia through the applied media. They also stated that the use of podcast can boost the learning atmosphere.